Surface nanodeformations caused by ultrashort laser pulse. (January 2015) - Inogamov, N.A.; Zhakhovsky, V.V.; Ashitkov, S.I.; Emirov, Yu.N.; Faenov, A.Ya.; Petrov, Yu.V.; Khokhlov, V.A.; Ishino, M.; Demaske, B.J.; Tanaka, M.; Hasegawa, N.; Nishikino, M.; et al.
Highlights: Ultrashort laser pulse causes strong foaming of irradiated metal. Fast non-equilibrium re-crystallization freezes jets and undersurface nanobubbles. After X-ray irradiation the surface nanostructures are created by foaming and freezing processes with no plasmonic effects. Abstract: Ultrashort laser pulse is a unique nanometallurgical tool which operates at extreme conditions: ultimate strength of material, the smallest spatiotemporal scales, and nonequlibrium crystallization. Approaches to ultimate strength and to highly nonequlibrium crystallization are tightly coupled with the smallness of spatiotemporal scales. Usage of the tool opens new opportunities to create materials with enhanced surface hardness, anticorrosion properties, and diverted optical constants. To use these advantages we have first of all to develop clear and reliable physical model. The paper presents new results concerning interactions of optical or X-ray lasers with metals. It is shown that ultrashort laser pulse melts surface layer, sends shock into bulk, and foams molten metal. Dense dislocation bilayer is created thanks to fast recrystallization (the first sublayer) and plastic transformations behind strong shock (the second sublayer). Plastic shock generated at moderate laser intensities attenuates sharply during its propagation into metal. During this attenuation, a plastic shock regenerates into a powerful elastic shock. This process defines boundary between the second dislocation sublayer and undamaged solid. Mechanical breaking of foam after its strong stretching and fly away of a part of melt together with fast freezing are responsible for appearance of chaotic frozen nanostructures at an irradiated surface.